Photocatalytic and antimicrobial activities of fluorine doped TiO2-carbon nano cones and disc composites. (March 2015) - Sangari, M.; Umadevi, M.; Mayandi, J.; Anitha, K.; Pinheiro, Jean Patrick
Abstract: Carbon nano cone and disc-fluorine-co-doped-titanium dioxide nanocomposites were synthesized by the solid state method. The physical and chemical properties of the prepared nanocomposites were characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR) and field emission-scanning electron microscopic (FE-SEM) techniques. In addition, a detailed study of antimicrobial activity and photocatalytic activity of the prepared nanoparticles were tested for its efficiency. Carbon cone and disc-doping into TiO2 showed not only the improvement in UV light absorption, but also in the creation of surface oxygen vacancies. Fluorine-doping produced several beneficial effects, including the formation of surface oxygen vacancies and the enhancement of Ti 3+ ions. XRD analysis showed the formation of TiO2 anatase phase in all cases. FE-SEM image, Fig. 3 d revealed irregular shapes of carbon cone and disc. The photocatalytic tests indicated that the carbon cone and disc-fluorine-co-doped TiO2 nanocubes have high UV light activity in degradation of methyl orange, which could be attributed to the creation of oxygen vacancies, increase the concentration of OH radicals in the solution, which is beneficial for improving the photodegradation rate of organic compounds. The carbon cone and disc-fluorine-TiO2 nanocomposites act as a strong antibacterial agent.